Development Of Modern Educational Infrastructure Based On The Principles Of Qs. Al-Rahman 33: Unifying Technology And Social Responsibility For Quality Education In Indonesia - Jamilatus Zahroh; Firdah Ni'matus Sholihah; Indah Rahayu; Moch Tolchah (Institut Agama Islam An-Nawawi Purworejo, 2025)
The development of modern educational infrastructure in Indonesia faces challenges in integrating technological advances with social responsibility. This research explores the principles of Q.S Al-Rahman verse 33 as an ethical and spiritual foundation in the development of sustainable and equitable educational infrastructure. The verse emphasizes the importance of a balance between human ability to break through the boundaries (through technology) and moral responsibility in its use. This article answers the question: How can the principles of Q.S Al-Rahman 33 be a guide in the development of modern educational infrastructure in Indonesia? This study uses a qualitative method with a literature study approach and thematic interpretation. Data was collected through a study of Qur'an interpretation, educational literature, government policies, and case studies on the application of technology in education. The research sample includes academic documents, reports of educational institutions, and the views of contemporary scholars on science and technology in Islam. The findings of the study show that Q.S Al-Rahman 33 offers an integrative framework between technological innovation and social responsibility, with three main principles: (1) the use of technology for the benefit of education, (2) strengthening inclusive access for all levels of society, and (3) mitigating negative impacts such as digital divides. Its implementation requires collaboration between the government, educational institutions, and the community. The conclusion of the study emphasizes that the Qur'anic value-based approach can strengthen the sustainability of educational infrastructure development in Indonesia. The contribution of this paper lies in providing a holistic Islamic perspective on modern education issues, while offering theoretical solutions for a more equitable and ethical education policy.